Ethical decision making for risky behaviors: A model for school counseling in Turkey | [Riskli davranışlara yönelik etik karar verme: Okul psikolojik danışmanları için bir model önerisi] - Ozdemir, Nurten Karacan; İyiaydın, Ayşegül Aracı (Ankara University, 2019)
In Turkey, there is not a great deal of research about ethical dilemmas and ethical decision-making mechanisms for school counselors; yet existing studies reveal difficulties school counselors face when handling difficult situations. The current paper proposes a culture-specific, including systemic and legal considerations, ethical-decision making model for school counselors in Turkey for risky behaviors of the students. The proposed model is based on the current situation regarding ethical issues in school counseling in Turkey with reference to the TPCGA, ASCA, and ACA ethical guidelines. A case example was provided, followed by further recommendations for policy, research, and practice. © 2019, Ankara University. All rights reserved.
Keywords: Ethical decision-making; Ethical dilemmas; Risky behaviors; School counseling